Carbimazole-induced agranulocytosis treated with propylthiouracil (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Antithyroid drugs may result in serious adverse events which require prompt alteration of therapy and adequate supportive measures. A 29-year-old female patient presented with a history of swelling in front of her neck for 3 months and cough, sore throat, and palpitation for 1 month. She was diagnosed as a case of Hyperthyroidism and was prescribed carbimazole 15 mg thrice daily. She was relatively well for 2 weeks with medications but after that, she experienced high-grade fever with chills and rigors associated with sore throat. Then she consulted with an Endocrinologist and was started on granulocyte colony-stimulating factor (G-CSF) with discontinuation of carbimazole. Barrier nursing and a broad-spectrum antibiotic (3rd generation cephalosporins) were used to treat her neutropenic sepsis and propylthiouracil was initiated. Her symptoms resolve following radio-iodine ablation and her thyroid function status is currently euthyroid.J Assoc Clin Endocrinol Diabetol Bangladesh, January 2022; 1 (1): 35-37